2015
DOI: 10.17116/otorino201580541-45
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of nasal bleeding in the patients presenting with arterial hypertension

Abstract: The objective of the present work was to study the pathogenetic mechanisms underlying nasal bleeding (NB) in the patients presenting with arterial hypertension (AH). A total of 47 patients with AH suffering from NB were available for the examination of whom 28 experienced a single bleeding episode and 19 had recurrent bleeding. 11 of them were treated by endonasal surgical intervention for the achievement of hemostasis. Simultaneously, mucoperichondreal biopsies were taken from the anterior septal portions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 6 publications
(6 reference statements)
0
2
0
1
Order By: Relevance
“…Periodontal microorganisms may directly invade the arterial wall, leading to vascular in ammation and atherosclerosis [36]. At the same time, the causes of vascular bleeding due to hypertension are directly related to endothelial lesions, microcirculatory disorders and alterations in the coagulation process, rather than to mechanical rupture of blood vessels, and these changes are thought to be responsible for the development of local intravascular coagulation [37]. Conversely, there are studies that do not support the link, with one nding that periodontal pockets and bleeding gums do not appear to be associated with high blood pressure in non-diabetic, non-smokers aged 30-49 years [38].…”
Section: Discussionmentioning
confidence: 99%
“…Periodontal microorganisms may directly invade the arterial wall, leading to vascular in ammation and atherosclerosis [36]. At the same time, the causes of vascular bleeding due to hypertension are directly related to endothelial lesions, microcirculatory disorders and alterations in the coagulation process, rather than to mechanical rupture of blood vessels, and these changes are thought to be responsible for the development of local intravascular coagulation [37]. Conversely, there are studies that do not support the link, with one nding that periodontal pockets and bleeding gums do not appear to be associated with high blood pressure in non-diabetic, non-smokers aged 30-49 years [38].…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported that hypertension increased platelet aggregation and activity, thereby activating the fibrinolytic system, which led to increased bleeding risk ( 19 ). A study also found that hypertension was directly related to vascular endothelial lesions, microcirculatory disorders, and modification of the blood coagulation processes ( 20 ). In addition, 24 patients had adverse bleeding events in the DBP <80 mm Hg group.…”
Section: Discussionmentioning
confidence: 99%
“…Превалирующие причины возникновения НК зависят от возраста пациента. Если у взрослых это артериальная гипертензия [8], то у детей НК чаще всего возникают в результате острой респираторной вирусной инфекции (ОРВИ) и сопряженного с ней приема нестероидных противовоспалительных препаратов [9] или пальцевой травмы на фоне образования корок в носу [1].…”
Section:  введениеunclassified